CIRFF 2015 - Conférence publique: «Race, colonialité & politique» avec Paola Bacchetta (2015)
Conférence de Paola Bacchetta, Université de Californie à Berkeley à la conférence publique «Race, colonialité et politique» organisée en collaboration avec l’Institut Simone-De Beauvoir au Congrès CIRFF2015, mercredi 26 août 2015, UQAM. 7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) http://cirff2015.uqam.ca/ 24 au 28 août 2015, Université du Québec à Montréal.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiracisme; approches et analyses; asie; autochtones; décolonialisme; féminisme décolonial; genre; identités LGBTQIA2+; inde; politique; périodes historiques; queer; québec; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Partenariats pluriels: le polyamour dans trois romans québécois, suivi de Au 5e, roman d'amours - Boisvert, Marie-Pier; Boisclair, Isabelle (Université de Sherbrooke, 2015)
Présenté en deux parties, un essai et une création, ce mémoire se veut une première exploration de la présence du polyamour dans la littérature québécoise. Alors que la monogamie règne toujours en maître du « vécurent heureux et eurent beaucoup d’enfants » dans la plupart des fictions littéraires, le modèle polyamoureux – posant qu’il est possible et acceptable d’aimer plus d’une personne et d’entretenir plusieurs relations amoureuses à la fois – s’inscrit comme un nouveau possible. Considérant ce modèle comme une critique de la monogamie institutionnelle et de la contrainte à cette dernière (ou mononormavité), la présente recherche étudie la représentation du polyamour dans trois romans québécois : C’est la faute au bonheur d’Arlette Fortin (2001), Ainsi font-elles toutes de Clara Ness (2005) et Tarquimpol de Serge Lamothe (2007). L’étude du nombre de partenaires impliqués, de leur configuration et du contrat établi dans chaque cellule amoureuse permet de mettre en lumière les éléments communs ou exclusifs à chaque récit et de comparer leurs discours. L’essai est suivi d’un court roman racontant l’irruption d’une cinquième personne dans un appartement où les colocataires partagent déjà leur amour, leurs ressources et, occasionnellement, leur sexualité. Cette création se pose à la fois en continuation et en opposition avec les romans étudiés, en évitant les pièges hétéronormatifs présents dans ces derniers, et en intégrant le polyamour dans le quotidien des personnages.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail social; trs1205

Exile and pride: Disability, queerness, and liberation - Clare, Eli (Duke University Press, 2015)
Publié pour la première fois en 1999, le révolutionnaire Exile and Pride est essentiel à l'histoire et à l'avenir de la politique des personnes handicapées. L'écriture révélatrice d'Eli Clare sur ses expériences en tant qu'activiste/écrivain genderqueer handicapé blanc l'a établi comme l'un des principaux écrivains sur les intersections de la queerness et du handicap et a changé de façon permanente le paysage de la politique du handicap et de la libération queer. Avec le dévouement d'un poète à la vérité et l'exigence de justice d'un activiste, Clare déroule habilement les multiples histoires à partir desquelles se déploie notre sens de soi en constante évolution. Ses essais mêlent mémoires, histoire et pensée politique pour explorer les significations et les expériences du chez-soi : le chez-soi en tant que lieu, communauté, corps, identité et activisme. Ici, les lecteurs trouveront un cadre intersectionnel pour comprendre comment nous vivons réellement avec l'hydraulique quotidienne de l'oppression, du pouvoir et de la résistance. À la base de l'exploration de Clare sur la destruction de l'environnement et le capitalisme, la sexualité et la violence institutionnelle, le genre et le corps politique, se trouve un appel à des mouvements de justice sociale véritablement accessibles
Keywords: approches et analyses; capacitisme; corps; cours; fem1300; identités LGBTQIA2+; militance; premier cycle; queer; thématiques

Transidentités: ordre & panique de genre : le réel et ses interprétations - Espineira, Karine; Bertini, Marie-Joseph (Collection Logiques sociales. Série Sociologie du genre, 2015)
Engagée dans une recherche sur le terrain transidentitaire, la chercheuse s'attache à croiser état des lieux du terrain associatif et militant trans avec l'histoire des définitions de la médecine légale, mettant à jour la politisation des groupes, les apports des nouveaux médias et les effets de la médiatisation sur les personnes transgenres. Cet ouvrage est complémentaire du titre Médiacultures: la transidentité en télévision, édité simultanément.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; histoire et politique; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; transféminisme

20e anniversaire! Héritages féministes : tensions et parallèles - Institut de recherches et d'études féministes (FéminÉtudes, 2015)
Cette publication célèbre les 20 ans de FéminÉtudes et revient sur les moments forts de la revue. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; féminétudes; genre; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; militance; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; écriture des femmes*

L'esthétique rock queer : de C.R.A.Z.Y. à Xavier Dolan - Laverdière, Gabriel (Nouvelles vues. Revue sur les pratiques et les théories du cinéma au Québec, 2015)
L'analyse proposée des films C.R.A.Z.Y. (Jean-Marc Vallée, 2005), J'ai tué ma mère (Xavier Dolan, 2009), Les amours imaginaires (Dolan, 2010) et Laurence Anyways (Dolan, 2012) convoque trois perspectives : le rock, le camp et le queer. Dans ces films québécois, la musique rock semble orienter la narration et l'esthétique. Elle fait également le pont entre l'anticonformisme auquel renvoie le paradigme rock et l'identité marginale des personnages. L'esthétique de l'image se plie parfois à la bande sonore, qui encourage certains effets visuels. Cela dit, les films de Vallée et de Dolan se servent différemment de l'esthétique rock et du camp, ce qui s'accorde aux représentations distinctes qu'ils produisent eu égard à l'orientation ou à la diversité sexuelles et au genre. L'excès des films de Dolan, leur hyperréférentialité, leur jeu constant entre recherche d'émotions esthétiques et d'émois narratifs, leur fréquente suspension de la réalité contribuent à une écriture du différé dans laquelle les personnages queer jouissent d'une amplitude considérable, alors que dans C.R.A.Z.Y. la performance hyperbolique s'articule plutôt à une analytique de l'homophobie (sociétale et intériorisée) que le film s'efforce de dresser, sans pouvoir échapper à un certain malaise.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; DIG; LGBTQIA2+; amériques; approches et analyses; arts; cinéma; communication; discipline; diversité sexuelle; genre; homophobie; identités LGBTQIA2+; musique; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sexualité; sofia; thématiques

Celebrating queer lesbian desires with Dorothy Allison: From moral monstrosity to the beautiful materiality of the body - Mélanie Grué (2015)
Using social and queer theory on domination, sexuality and gender, this contribution explores how the queer American author Dorothy Allison celebrates the vilified transgressive lesbian body. As, in the 1970s, the mainstream american feminist movement crystallized around the definition of an acceptable sexuality in the name of femininity, female sexual practices were standardized according to strict identity frames, carnal desire was denied, and transgressive lesbians who play with gender roles were defined as abject. In response to this extreme taming of the body, Allison interrogates the notions of masculinity and femininity, domination and submission in her exploration of sexual pleasure and traumatized sexuality. She celebrates the aggressiveness and masculinity of queer lesbianism, promotes the fluidity of gender roles, and asserts the primacy of the flesh,sensuality, and materiality in sexuality.
Keywords: approches et analyses; arts; corps; corps lesbien; discipline; identités LGBTQIA2+; littérature; personnes lesbiennes; queer; ressource en ligne; sexualité; thématiques; études littéraires

Language and masculinities: performances, intersections, dislocations - Milan, Tommaso M. (Routledge critical studies in discourse, 2015)
This volume showcases cutting-edge research in the linguistic and discursive study of masculinities, comprising the first significant edited collection on language and masculinities since Johnson and Meinhof’s 1997 volume. Overall, the chapters are linked together by a critical analytical perspective that seeks to understand the relationships between discourse, masculinities, and power. Whereas some of the chapters offer detailed, linguistically informed critiques of the ways in which old and new expressions of masculinities are complicit in the reproduction of men’s hegemonic positions of power, others provide a more complex picture, one in which collusion and subversion go hand in hand. Contributions argue for the need for research on language and masculinities to expand its remit so as to engage with "gay masculinities," and unsettle gendered categories in order to consider the ways in which women, transgender, and intersex individuals also perform a variety of masculinities. Finally, unlike Johnson and Meinhof’s 1997 collection, this volume not only offers a wider—and perhaps "queerer" perspective—on the study of language and masculinities, but also covers a broader geographical and socio-cultural spectrum, including work on Brazil, Israel, New Zealand, Singapore, and South Africa.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; masculinité; premier cycle; queer; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociolinguistique; sofia; thématiques; études de genres

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques

Dirty river: A queer femme of color dreaming her way home - Piepzna-Samarasinha, Leah Lakshmi (Arsenal Pulp Press, 2015)
Finaliste du Prix littéraire Lambda et du Prix Judy Grahn pour la non-fiction lesbienne En 1996, la poète Leah Lakshmi Piepzna-Samarasinha, portant seulement deux sacs à dos, a pris un bus Greyhound en Amérique et s'est enfuie au Canada. Iel s'est retrouvé.e à Toronto, où iel a été accueilli.e par une communauté de punks queer de couleur offrant des promesses d'amour et de révolution, mais iel est resté.e hanté.e par les raisons pour lesquelles iel a quitté la maison en premier lieu. Ce mémoire passionné et captivant est un mélange de rêves et de cauchemars, de files d'attente devant les tribunaux de l'immigration et de soirées dansantes queer sud-asiatiques ; Il s'agit d'une feuille de route intensément personnelle et d'un récit tragi-comique intersectionnel qui révèle comment une femme queer handicapée de couleur et survivante d'abus navigue sur la rivière sale d'un passé pas si lointain et, comme le suggère le sous-titre, « rêve de rentrer chez elle ». "
Keywords: amériques; approches et analyses; canada; capacitisme; identités LGBTQIA2+; mémoire collective; queer; queer of color; racisme; récit de vie; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; états-unis

Esthétique(s) "queer" dans la littérature et les arts: sexualités et politiques du trouble - Plana, Muriel; Sounac, Frédéric (1969- ...).; Beauchamp, Hélène (1977- ...).; Bret-Vitoz, Renaud (1972- ...).; Garnier, Emmanuelle (1964- ...).; Plana, Muriel; Sounac, Frédéric; Beauchamp, Hélène; Bret-Vitoz, Renaud; Garnier, Emmanuelle (Écritures, 1630-0858, 2015)
"En important dans le champ de l'esthétique le concept de "queer" issu des pensées du genre et en s'inscrivant dans une perspective interdisciplinaire, tant du point de vue des arts étudiés (littérature, arts de la scène, du corps et de l'image) et des méthodes adoptées (approches littéraires, sociocritique, philosophie, "gender studies", "women studies", "queer studies" ...), cet ouvrage collectif s'attache à ce qui, dans des productions artistiques contemporaines mais aussi plus anciennes, tend à jeter le trouble, politiquement et formellement, dans la représentation des identités sexuelles, des sexualités et de l'érotisme. Le livre fait par conséquent le pari que le travail des écrivains et des artistes autour du travestissement et des homosexualités ou encore leur intérêt pour la représentation de phénomènes comme le transgenre ou le "transsexualisme" leur permettent de penser ou de repenser, entre transgression et subversion, les concepts de "queer" et d'"esthétique", ainsi que de transformer radicalement nos représentations et notre façon d'envisager l'histoire des arts, des idées et des sociétés." [Source : 4e de couv.].
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; esthétique; har4600; histoire de l'art; identités LGBTQIA2+; philosophie; premier cycle; queer; sciences humaines; thématiques; théorie de l'art

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle